Ozonolytic synthesis of 2-hydroxybenzyl alcohol for the production of gastrodin - A. H. Halstian; A. S. Hasanova; H. V. Tarasenko (Zaporozhye State Medical University, 2023)
2-Hydroxybenzyl alcohol is an important active pharmaceutical ingredient for the production of many drugs, in particular gastrodin, which has a wide range of beneficial effects on epilepsy, Alzheimer's disease, Parkinson's disease, affective disorders, cerebral ischemia, cognitive disorders. It is known that 2- and 4-hydroxybenzyl alcohols and mixtures of both compounds are obtained by the interaction of phenol with formaldehyde in the presence of basic catalysts. Due to its high reactivity with formaldehyde, the isolation of pure compounds from the reaction mixtures obtained during the interaction of phenol with formaldehyde is a big problem. Isolation of 2-hydroxybenzyl alcohol in pure form from reaction mixtures is possible only using processes that cannot be carried out on an industrial scale and is accompanied by low yields of the target product. It is possible to get rid of these problems by means of the process of direct oxidation of the 2-hydroxytoluene with ozone in the liquid phase since methods of selective ozonation of methylbenzene to the oxygen derivatives are already known. Therefore, the development of a new low-temperature synthesis of 2-hydroxybenzyl alcohol using ozone is an urgent task. The aim of the work is to study the reaction of the oxidation of 2-hydroxytoluene by ozone in a solution of a stop reagent and catalytic impurities of compounds of transition metals and mineral acids for the development of a new method of synthesis of 2-hydroxybenzyl alcohol. Materials and methods. For the experiments, acetic anhydride of p. a. qualification was used; glacial acetic acid of puriss. qualification, which before use was purified by distillation under vacuum in the presence of potassium permanganate, 2-hydroxytoluene of puriss. Qualification, manganese (II) acetate of pur. Qualification, sulfuric and phosphoric acids of puriss. qualification. To determine the concentration of ozone in the gas phase, a spectrophotometric method was used, based on the measurement of the optical density of the gas flow in the UV region. For this purpose, a spectrophotometer SF-46 LOMO was used, in the measuring chamber of which a flow cuvette with quartz windows was installed. The material of the cuvette was Teflon. Continuous monitoring of the current concentration of ozone, with the recording of the analysis results in the form of a kinetic curve, was carried out when ozone-containing gas passed through the curette at a certain wavelength of a monochromatic light source. Results. The reaction of oxidation of 2-hydroxytoluene by ozone in a solution of the stop reagent - acetic anhydride was studied. It was shown that in the presence of sulfuric acid, it was possible to carry out direct ozonation of 2-hydroxytoluene to 2-hydroxybenzyl alcohol, which was formed in the kind of 2-acetoxybenzyl acetate with a yield of 13.0 %. The main products of the reaction under these conditions are aliphatic compounds, which are formed after the destruction of the aromatic ring. The selectivity of oxidation by alcohol was significantly increased when a catalyst - manganese (II) acetate - was added to the system. In its presence, a catalytic system As2O - H2SO4 - Mn(III) was created, which prevents ozonolysis and directed oxidation mainly to the methyl group of the substrate with the formation of 2-acetoxybenzyl acetate with a yield of 63.2 %. Conclusions. An environmentally friendly, low-temperature method for the synthesis of 2-hydroxybenzyl alcohol was developed by conducting the oxidation of 2-hydroxytoluene with ozone in a solution of the stop reagent - acetic anhydride in the presence of sulfuric acid and manganese (II) acetate.